The Circular Economy's Performance and the Impact of Digitalization - Khong, Isaac (International Transactions on Education Technology (ITEE), 2023)
The acceleration of economic transition towards a more sustainable circular production system is a pressing global concern. This study addresses the scarcity of empirical research on the impact of digitization on circular economy efficiency. It investigates the influence of digitization on the effectiveness of circular economy practices through an empirical analysis of quantitative data obtained from 200 participants within the financial sector of Kozani, Greece. The results, derived from regression analysis, reveal a significant and positive association between digital business practices and circular economy performance. Notably, industrial firms that prioritize digitalization exhibit a notably higher adoption rate of new business innovations for resource efficiency. These findings underscore the strong connection between digitalization and circular economy performance, highlighting the potential for digitalization to catalyze the development of circular business models. This research contributes to our understanding of the pivotal role that digitization plays in advancing sustainable circular economies